2020
DOI: 10.1371/journal.pone.0234604
|View full text |Cite
|
Sign up to set email alerts
|

Ability self-concept and self-efficacy in higher education: An empirical differentiation based on their factorial structure

Abstract: Ability self-concept (SC) and self-efficacy (SE) are central competence-related self-perceptions that affect students' success in educational settings. Both constructs show conceptual differences but their empirical differentiation in higher education has not been sufficiently demonstrated. In the present study, we investigated the empirical differentiation of SC and SE in higher education with N = 1,243 German psychology students (81% female; age M = 23.62 years), taking into account central methodological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 107 publications
1
6
0
3
Order By: Relevance
“…The third finding of this study indicated that most students positively perceived ES lecturers' efforts because such efforts were beneficial to the improvement of their motivation, self-efficacy, collaborative skills, and metacognition. Studies have identified that motivation and self-efficacy exist within the same psychological domain (Bragina & Voelcker-Rehage, 2018;Peiffer et al, 2020). Supporting the present study, Truong and Wang (2019) highlighted that teachers' efforts are needed to improve students' motivation and self-efficacy.…”
Section: Discussionsupporting
confidence: 73%
“…The third finding of this study indicated that most students positively perceived ES lecturers' efforts because such efforts were beneficial to the improvement of their motivation, self-efficacy, collaborative skills, and metacognition. Studies have identified that motivation and self-efficacy exist within the same psychological domain (Bragina & Voelcker-Rehage, 2018;Peiffer et al, 2020). Supporting the present study, Truong and Wang (2019) highlighted that teachers' efforts are needed to improve students' motivation and self-efficacy.…”
Section: Discussionsupporting
confidence: 73%
“…It also brings up the critical question to what extent manageability and social support are distinct constructs or perhaps have strong analogous characteristics. In several research studies, theoretical constructs, such as self-concepts and self-efficacy, overlap, and researchers often struggle to decipher the distinctive characteristics (Bong & Skaalvik, 2003;Peiffer et al, 2020). Throughout the health-related literature, sound, programmatic approaches are offered, but mostly there is only a loose reference to salutogenesis (Bauer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Apa yang diyakini individu terhadap kemampuannya akan membuat mereka mudah menyesuaikan diri dengan sejumlah tuntutan yang dihadapi. Peiffer, Ellwart, & Preckel (2020) menyebutkan bahwa self efficacy hanya terdiri dari komponen kognitif.…”
Section: Pembahasanunclassified